The characteristics of lower extremity muscle activity and static balance of Chinese elite trampoline athletes during net contact phase - Liu, Kai; Zhu, Zhangbiao; Yang, Tong; Yin, Jun (Frontiers in Physiology, 2026)
Lower extremity muscle strength and balance control are crucial components in high-level trampolining. However, current research on these aspects remains limited. This study aimed to explore the activity patterns of lower limb muscle groups and the balance characteristics of elite trampoline athletes in China, with a focus on comparing male and female athletes. Eleven elite trampolining athletes from the China national team (age: 23.42 ± 4.40 years; height: 165.37 ± 4.33 cm; weight: 53.38 ± 3.42 kg; training duration: 8.3 ± 2.61 years; M/F: 5/6) were required to test the electromyography (EMG), static balance, and plantar pressure. The Two-way ANOVA was adopted to compare the differences between sexes and lower limbs. The results showed significant gender differences in muscle activity during the net contact stage. Male athletes had higher Root Mean Square (RMS) values for the gastrocnemius (P < 0.01), with significant left-right differences in contribution rates (P < 0.05). In static balance, female athletes showed stronger right-side balance under closed-eye conditions (P < 0.05), while male athletes had stronger left-side balance under open-eye conditions (P < 0.01). Additionally, male athletes exhibited higher total plantar pressure on the left side (P < 0.01). This study reveals that during the net contact phase, male and female athletes exhibit distinct lower limb dynamics, with males showing a leftward shift in center of gravity and significant right ankle force, while both genders demonstrate heel-dominant plantar pressure and left-right balance differences, emphasizing the need for targeted unilateral balance and right ankle explosive strength training.